ORIENTASI PEMAHAMAN PENGARUH AZ-ZAMZAMI BAGI DINAMIKA ‘ULÛM AL-QUR’AN DI UNIVERSITAS PTIQ JAKARTA - Nasaruddin Umar; Made Saihu; Abdur Rokhim Hasan; Zainal Abidin; M. Suaib Tahir; Fina Lailatul Masruroh (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This article explains the important role of 'Abd al-Aziz Az-Zamzami (d. 976 H) in the field of Qur’anic science. The writing is motivated by the position of As-Suyuthi (d. 911 H), who is considered a prominent figure, even a legend in this field. This significant position is both appreciated and criticized. One strong criticism is that post-As-Suyuthi works are merely repetitive. As a result, post-As-Suyuthi figures who write works on Qur’anic science are no longer highlighted, and their roles are marginalized. They will find it difficult to emerge from As-Suyuthi's shadow. One of these figures is 'Abd al-Aziz Az-Zamzami. Through historical research, this work goes through the following stages: first, excavating historical sources, second, verifying sources, and third, interpreting and explaining history. This qualitative research explores credible historical sources based on literature. The result is that Az-Zamzami is a literary figure who adapts As-Suyuthi's work titled An-Niqâyah, in the chapter of exegesis into concise, dense, full of literary value, and easily memorized verses. Az-Zamzami's work is titled Manzhûmah at-Tafsir and has been responded to by 18 scholars from around the world, including from Indonesia. The birth of these several explanations indicates that versification has become part of a teaching strategy considered relevant and worthy of explanation. From these findings, it is concluded that Az-Zamzami's work is indeed always related to As-Suyuthi's work, but he can also be seen as a figure standing on his own